COMPARISON OF THE TOOTH BRUSHING HABITS OF PRIMARY SCHOOL AGE CHILDREN AND THEIR PARENTS - Ceren Damla Özbek (Journal of Istanbul University Faculty of Dentistry, 2015)
Purpose: As they grow, children develop their attitude and behavior related to tooth brushing by taking their parents’ oral-dental health behavior as an example. The purpose of this study was to assess whether there was a similarity in tooth brushing between primary school-age children and their parents presenting to the Department of Oral, Dental and Jaw Diseases and Surgery and the Department of Pedodontics, School of Dental Medicine, Istanbul University. Patients and Methods: The study included 126 children and their parents, as totally 252 subjects. The data on oral hygiene of the subjects were obtained using a questionnaire form including questions on the qualitative-quantitative tooth brushing habits of the children and their parents and the socio-demographic characteristics of their families. Results: In most of the cases, there was a similarity between children and their parents in terms of frequency of dentist visits, the therapy they underwent in their last dentist visit, the cause of caries, the frequency of tooth brushing, the material used for oral hygiene, the duration of tooth brushing, method of tooth brushing, and tooth sites most brushed, which showed a significant association between children and their parents (p<0.01). Conclusion: Correct knowledge given to the children by their families will positively affect the oral-dental health of the children. Thus, firstly, correct knowledge should be given to the parents so that they can successfully carry out their responsibility in being the correct model for their children in oral-dental health.